The Impacts of COVID-19 on US Maternity Care Practices: A Followup Study - Gutschow, Kim; Davis-Floyd, Robbie (Frontiers in Sociology, 2021)
This article extends the findings of a rapid response article researched in April 2020 to illustrate how providers’ practices and attitudes towards COVID-19 had shifted in response to better evidence, increased experience, and improved guidance on how SARS-CoV-2 and COVID-19 impacted maternity care in the US. This article is based on a review of current labor and delivery guidelines in relation to SARS-CoV-2 and COVID-19, and on an email survey of 28 community-based and hospital-based maternity care providers in the US, who discuss their experiences and clients’ needs in response to a rapidly shifting landscape of maternity care during the COVID-19 pandemic. One-third of our respondents are obstetricians, while the other two-thirds include midwives, doulas, and labor & delivery nurses. We present these providers’ frustrations and coping mechanisms in shifting their practices in relation to COVID-19. The primary lessons learned relate to improved testing and accessing PPE for providers and clients; the need for better integration between community- and hospital-based providers; and changes in restrictive protocols concerning labor support persons, rooming-in with newborns, immediate skin-to-skin contact, and breastfeeding. We address how changing practices and protocols influenced mother’s and providers’ wellbeing. We conclude by suggesting that the COVID-19 pandemic offers a transformational moment to shift maternity care in the US towards a more integrated and sustainable model that can improve provider and childbearer experiences as well as maternal and newborn outcomes.